Long-Term Outcomes in Patients With Peripheral Arterial Disease Who Undergo Free Flap Reconstruction for Chronic Lower Extremity Wounds. Issue 1 (January 2023) - Bovill, John D.; Huffman, Samuel S.; Deldar, Romina; Sayyed, Adaah A.; Gupta, Nisha J.; Truong, Brian N.; Bekeny, Jenna C.; Attinger, Christopher E.; Akbari, Cameron N.; Evans, Karen K.
Abstract : Background: Free tissue transfer (FTT) is critical for limb salvage of chronic lower extremity (LE) wounds. In patients with peripheral arterial disease (PAD), FTT LE reconstruction can be challenging due to limited vessel selection for anastomosis. The study aims to evaluate our surgical and functional outcomes after FTT to LE in patients with PAD. Methods: A retrospective review identified patients who underwent LE free flap reconstruction between 2011 and 2021. All patients underwent preoperative arteriogram and subsequent FTT. Patients were classified into PAD or non-PAD cohorts, based on the presence of LE arterial stenoses or occlusions identified on arteriogram. Primary outcomes included complications, flap success, need for post-FTT vascular reintervention, limb salvage, and ambulatory status. Results: A total of 253 patients underwent FTT to LE, with 84 patients (33.2%) in the PAD cohort. Patients with PAD had a higher prevalence of diabetes (83.3% vs 39.1%, P < 0.001) and end-stage renal disease (8.3% vs 2.4%, P = 0.028). Osteomyelitis was more common in the PAD group (73.8% vs 55.0%, P = 0.004). Free tissue transfer donor sites and flap composition were similar between cohorts. At a mean follow-up of 21.1 months, limb salvage rates were similar between non-PAD and PAD cohorts (90.5% vs 84.5%, P = 0.158), with no significant differences in ambulatory status or mortality. Higher complication rates occurred in the PAD cohort (38.1% vs 20.7%, P = 0.003), of which partial flap necrosis was more prevalent in the PAD group (6.0% vs 0.6%, P = 0.016). There was no difference in flap success rates between groups ( P = 0.430). More postflap angiograms were performed in the PAD group (29.8% vs 7.1%, P < 0.001), with repeat percutaneous endovascular intervention performed in 68.0% of the PAD group versus 33.3% of the non-PAD group ( P < 0.001). Conclusions: This is the largest study to demonstrate excellent long-term limb salvage outcomes in patients with PAD who undergo FTT to LE. Percutaneous endovascular intervention and FTT are effective methods to achieve limb salvage in vasculopathic patients with chronic LE wounds.